Longevity of resin-bonded fixed partial dental prostheses made with metal alloys - Tanoue, Naomi (Clin Oral Investig, 2015)
OBJECTIVES: The purpose of this study was to evaluate the clinical performance of resin-bonded fixed partial dental prostheses (RBFPDPs) made with metal alloys. MATERIALS AND METHODS: The retention of 311 RBFPDPs from 226 patients fabricated from 1983 to 2013 using an adhesive resin was clinically evaluated. Partial or complete debonding of the RBFPDP or framework fracture was considered a treatment failure. All data were obtained from clinical examinations, and missing data were censored at the date of the last available information. The effect of the following factors on survival rate were investigated: patient gender, location (maxilla/mandible and anterior/posterior), number of missing teeth, number of abutment teeth, framework structure, type of metal alloy, patient age at the point of cementation, cement type, and distinction of the treating dentist. Data were analyzed with the Kaplan–Meier survival tests, log-rank tests, and Cox regression analyses (α = 0.05). RESULTS: The Kaplan–Meier survival rate was 41.2 % ± 6.5 % (standard error) at 28.8 years (last outcome event). Significant differences were found for patient age and treating dentist (p < 0.05). The risk of failure in younger patients was 1.7 times greater than that in older patients and that of inexperienced dentists was 2.0 times greater than that of dentist experienced and specialized in adhesive dentistry. CONCLUSIONS: When fabricating RBFPDPs for younger patients, mechanical preparation for bonding may be necessary in consideration of the risk for debonding. Experienced dentists may achieve better results. CLINICAL RELEVANCE: Mastery of skills is necessary to ensure excellent prognoses for RBFPDPs.